Operant EEG-based BMI: Learning and consolidating device control with brain activity - Loureiro, Nuno (2022)
"Whether you are reading this thesis on paper or screen, it is easy to take for granted all the highly specialized movements you are doing at this very moment just to go through each page. Just to turn a page, you have to reach for and grasp it, turn it and let go at the precise moment not to rip it.(...)"